2014
DOI: 10.1039/c4ta00674g
|View full text |Cite
|
Sign up to set email alerts
|

A facile preparation method of surface patterned polymer electrolyte membranes for fuel cell applications

Abstract: We report a facile universal patterning method that provides well-arrayed patterns of polymer electrolyte membranes with a large electrochemical area using an elastomeric mold. The membrane electrode assembly fabricated with patterned Nafion membrane exhibited a high current density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 42 publications
2
59
1
Order By: Relevance
“…This became in particular evident using electrodes with low Pt-loading, where at high current densities a strong deviation was observed between a CCM and DMD sample in the iR-free representation. In recent literature new concepts with patterned membranes revealed that in spite of identical membrane thickness a modified catalystemembrane interface can strongly improve the cell performance [28,29]. These observations are in good agreement with the observed characteristics of DMD fuel cells.…”
Section: Resultssupporting
confidence: 70%
“…This became in particular evident using electrodes with low Pt-loading, where at high current densities a strong deviation was observed between a CCM and DMD sample in the iR-free representation. In recent literature new concepts with patterned membranes revealed that in spite of identical membrane thickness a modified catalystemembrane interface can strongly improve the cell performance [28,29]. These observations are in good agreement with the observed characteristics of DMD fuel cells.…”
Section: Resultssupporting
confidence: 70%
“…Conventional PEMFC architectures formed by sandwiching Nafion membranes and Pt‐based catalyst layers utilize these approaches for restructuring the MEA via membrane or catalyst layer patterning, and for the formation of ultra‐thin catalyst layers. The membrane patterning approach has been demonstrated with membrane laser ablation , plasma modification in Ar, H 2 ‐He, Ar‐O 2 , and Ar‐SF 6 environments , and lithographic patterning . Plasma deposited Pt gas diffusion electrodes and catalyst coated membranes , Pt films in conjunction with restructured membranes , and sputter‐patterned Pt electrodes via a glancing angle deposition approach have also been examined to illustrate the benefits of microfabrication to PEMFC cell construction.…”
Section: Introductionmentioning
confidence: 99%
“…This was linked to an improved interface between catalyst layers and membrane. [43,47] In previous work, this low R LF-HF was related to strong water Adv. [43,47] In previous work, this low R LF-HF was related to strong water Adv.…”
Section: Beginning Of Test/ End Of Test -Analysismentioning
confidence: 84%